Validation and Acceptability of the Mobile App Version of the Control of Allergic Rhinitis and Asthma Test for Children (CARATKids): Cross-Sectional Study - Dulce Abreu da Mata; Inês Pais-Cunha; Sandra Catarina Ferraz; Daniela da Rocha Couto; Catarina Ferraz; Sónia Silva; José Carlos Valente; Pedro Vieira-Marques; João A Fonseca; Inês Azevedo; Cristina Jácome (JMIR Pediatrics and Parenting)
Abstract BackgroundThe electronic version of the Control of Allergic Rhinitis and Asthma Test for Children (CARATKids) has the potential to enhance pediatric telemonitoring but has not yet been validated. ObjectiveThis study aimed to validate the electronic version of CARATKids against the paper-based version. MethodsA cross-sectional study was conducted between April and December 2024 in a tertiary hospital in northern Portugal. Children with asthma or allergic rhinitis and their caregivers were recruited during pulmonology outpatient appointments. CARATKids comprises 13 yes or no questions, 8 addressed to the child and 5 to the caregiver, and the total score ranges from 0 to 13. The electronic CARATKids was made available through a mobile app. Both paper and electronic versions were administered in a randomized order before and after the appointment. In addition, participants’ preferences between the two administration versions were assessed. Internal consistency (Cronbach α), reliability (intraclass correlation coefficient [ICC], Bland-Altman analysis), and convergent validity (Spearman coefficient) were analyzed following COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) guidelines. ResultsA total of 51 children (median 9, IQR 8-11 years; n=29, 57% male) and respective caregivers (median 41, IQR 7-45) years were included. The CARATKids total score was similar across the paper (median 5, IQR 3-8) and electronic (median 5, IQR 3-7) versions. The internal consistency was 0.79 for the paper version and 0.83 for the electronic version. The reliability between the two versions was excellent (ICC 0.95, 95% CI 0.91‐0.97). The Bland-Altman analysis showed strong agreement between the two versions, with a mean difference of 0.04 (95% CI −1.99 to 2.07). The Spearman correlation between the two versions was 0.95 (P ConclusionsThe electronic version of CARATKids appears to be equivalent to the paper-based version of the questionnaire, with good acceptance by children and caregivers. CARATKids implementation in mobile health technologies has the potential to enhance remote child monitoring and optimize the management of asthma and allergic rhinitis.